Therapeutic potential of Hedgehog signaling inhibitors in cancer: rationale and clinical data. (April 2012) - Aftab, Blake T; Rudin, Charles M
The Hedgehog (Hh)-signaling pathway has become recognized as a key therapeutic target in cancer. In addition to a recently approved first-in-class Hh-pathway inhibitor, several other small-molecule Hh inhibitors are currently under clinical investigation in a variety of cancer settings. Hh signaling occurs through both ligand-dependent and -independent signaling mechanisms and has been implicated in tumor propagation, maintenance of cancer cell stem niches, differentiation, metastatic potential and tumor-microenvironment interactions. Hh-pathway inhibitors have shown robust clinical efficacy in diseases driven by ligand-independent pathway activation. However, use of Hh antagonists in this setting may result in acquired drug-resistance. This reality poses interesting challenges for treating drug-resistant neoplasia. The rationales for therapeutic application of Hh-targeting agents beyond ligand-independent diseases are complex, and the positioning of Hh-targeted agents must consider context-dependent contributions to primary determinants of tumorigenesis and secondary contributions to tumor homeostasis in individual disease settings.